Indoor temperature and humidity prediction in residential buildings: A review of the white box and black box modeling techniques - Chima Cyril Hampo; Leah H. Schinasi; Simi Hoque (Building and Environment, 2026)

Residential indoor temperatures and health: A scoping review of observational studies - Janelle R. Edwards; Anneclaire J. De Roos; Chima C. Hampo; Wanyu Huang; Emily Lincoln; Simi Hoque; Leah H. Schinasi (Science of The Total Environment, 2025)

Towards healthy sleep environments: Ambient, indoor, and personal exposure to PM2.5 and its implications in children's sleep health - Yalin Lu; Ming Yan; Simi Hoque; Ignacio E. Tapia; Nan Ma (Environmental Research, 2025)

Machine learning to model gentrification: A synthesis of emerging forms - Mueller Maya; Hoque Simi; Hamil Pearsall (Computers, Environment and Urban Systems, 2024)

Investigating the application of a commercial and residential energy consumption prediction model for urban Planning scenarios with Machine Learning and Shapley Additive explanation methods - Shideh Shams Amiri; Maya Mueller; Simi Hoque (Energy and Buildings, 2023)

Resilience of environmental policy amidst the rise of conservative populism - Nariman Mostafavi; João Fiocchi; Manuel García Dellacasa; Simi Hoque (Journal of Environmental Studies and Sciences, 2022)
Sustainability has for long been promoted as a medium for social and economic development, one that focuses on constant availability of natural assets and ecological amenities. By questioning the possibility of reaching a balanced and sustainable state of functioning for social-ecological systems, resilience improves the static framework of sustainability by acknowledging non-linear behavior of complex systems, inevitability of change, and consistent presence of uncertainty. At the core of sustainable development, environmental policy is embedded in the socio-spatial structures that constantly re-organize and breed uncertainty, such as political, economic, and climate uncertainty. These uncertainties create episodes of instability that shock the entire system including the structures of environmental protection. In this article, focusing on the aftermath of 2016 US presidential election and 2018 general election in Brazil, both broadly recognized as political shocks, we highlight the vulnerabilities of environmental protection structures to the rise of conservative populist movements. We attribute these vulnerabilities, partially, to the superiority of market-based instruments, as well as apolitical understandings of resilience under neoliberalism that overlook political instabilities and socio-spatial outcomes of neoliberal restructuring projects. In our assessment, political unpreparedness of sustainability against the right-wing onslaught in the US and Brazil further underlines the need for resilience theory to incorporate sources of political instability in order to protect the environment.